Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1021/acsnano.1c02668
|View full text |Cite
|
Sign up to set email alerts
|

Highly Heterogeneous Polarization and Solvation of Gold Nanoparticles in Aqueous Electrolytes

Abstract: The performance of gold nanoparticles (NPs) in applications depends critically on the structure of the NP−solvent interface, at which the electrostatic surface polarization is one of the key characteristics that affects hydration, ionic adsorption, and electrochemical reactions. Here, we demonstrate significant effects of explicit metal polarizability on the solvation and electrostatic properties of bare gold NPs in aqueous electrolyte solutions of sodium salts of various anions (Cl − , BF 4 − , PF 6 − , nitro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 90 publications
3
9
0
Order By: Relevance
“…In particular, we observe only marginal differences in the profiles between metallic and nonmetallic graphite, in agreement with previous reports: [51][52][53][54] A slightly stronger orientation of the first water layer on metallic graphite can be deduced from the larger hydrogen number density for z < 0.05 nm in Fig. 5(d) and from the more negative average cos(θ) close to the GDS for z < 0.15 nm in Fig.…”
Section: Metallic Vs Nonmetallic Graphitesupporting
confidence: 92%
“…In particular, we observe only marginal differences in the profiles between metallic and nonmetallic graphite, in agreement with previous reports: [51][52][53][54] A slightly stronger orientation of the first water layer on metallic graphite can be deduced from the larger hydrogen number density for z < 0.05 nm in Fig. 5(d) and from the more negative average cos(θ) close to the GDS for z < 0.15 nm in Fig.…”
Section: Metallic Vs Nonmetallic Graphitesupporting
confidence: 92%
“… [29] The high capacitance is attributed to the specific adsorption/solvation that the ions adopt at the interface with a strongly metallic Au electrode. In agreement, another recent theoretical study on Au nanoparticles has found that specific ion adsorption provides significant effects on the induced polarization of the polarizable nanoparticle surface, [30] which has substantial effects on the electrostatic surface potentials and work function [31] and, thus, on the EDL capacitance.…”
Section: Resultssupporting
confidence: 76%
“…[5] However,avery recent study on gold-aqueous sodium chloride interfaces demonstrates the influence of the parameterization of the electrostatic parameters on the electrode/ electrolyte properties and shows that larger differential capacitances up to about 125 mFcm À2 can be obtained for strongly metallic electrodes by changing the width of the Gaussian charge distribution used to represent the atomic charges of the gold surface. [29] Theh igh capacitance is attributed to the specific adsorption/solvation that the ions adopt at the interface with astrongly metallic Au electrode.In agreement, another recent theoretical study on Au nanoparticles has found that specific ion adsorption provides significant effects on the induced polarization of the polarizable nanoparticle surface, [30] which has substantial effects on the electrostatic surface potentials and work function [31] and, thus,ont he EDL capacitance.…”
Section: Methodssupporting
confidence: 76%
“…The existence of charged ionic adlayers next to the NP surface suggests that adsorption patterns for biomolecules can be significantly impacted, especially when higher ion concentrations and polyvalent ions are present in the media as a result of interfacial polarization alterations predicted for polarizable NPs (e.g., noble metals). 73 …”
Section: Resultsmentioning
confidence: 99%
“…The existence of charged ionic adlayers next to the NP surface suggests that adsorption patterns for biomolecules can be significantly impacted, especially when higher ion concentrations and polyvalent ions are present in the media as a result of interfacial polarization alterations predicted for polarizable NPs (e.g., noble metals). 73 Computed PMF profiles (shown in Figures 4 and S1 in the Supporting Information) had no adsorption minima next to the NP surface (SSD < 0.15 nm), suggesting that adsorbates were not able to expel water molecules from the first hydration shell around the AgNP. However, they were able to penetrate through the second interfacial water layer.…”
Section: ■ Resultsmentioning
confidence: 99%